A singular relationship: the bonds between gestational carriers and intended parents in surrogacy between Ukraine and Argentina - Lucía Ariza; Natacha Salomé Lima (Salud Colectiva)
Surrogacy is a practice that generates controversy, especially in contexts where regulation is scarce or nonexistent. In Argentina, although there is no specific legislation, this practice involves significant judicial mediation and various legal strategies for its implementation. Local legal uncertainties have led many Argentine families to pursue surrogacy procedures in other countries, with Ukraine standing out as a prominent destination due to its accessibility and specific characteristics. This study aims to analyze, from the perspective of intended parents, the relationships between married cisheterosexual women who seek or have become mothers (intended parents) through surrogacy and Ukrainian gestational carriers. Using a qualitative-exploratory design, between 2022 and 2024, 18 in-depth interviews were conducted with individuals who had undergone surrogacy and traveled internationally for the process. The results show that the established bonds transcend geographical boundaries and are enriched by a bidirectional exchange of objects (photos, gifts, songs, among others) and emotions, shaping singular relationships. These findings contribute to a more nuanced understanding of surrogacy, moving beyond simplistic views that reduce it to the instrumentalization of women’s bodies and highlighting the relational and affective dimensions of these experiences.